1993
DOI: 10.1126/science.8378773
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of DNA Binding Proteins by Multiple Cytokines

Abstract: Interferon-alpha (IFN-alpha) and IFN-gamma regulate gene expression by tyrosine phosphorylation of several transcription factors that have the 91-kilodalton (p91) protein of interferon-stimulated gene factor-3 (ISGF-3) as a common component. Interferon-activated protein complexes bind enhancers present in the promoters of early response genes such as the high-affinity Fc gamma receptor gene (Fc gamma RI). Treatment of human peripheral blood monocytes or basophils with interleukin-3 (IL-3), IL-5, IL-10, or gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
0
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 358 publications
(167 citation statements)
references
References 11 publications
(10 reference statements)
9
157
0
1
Order By: Relevance
“…STAT proteins can interact with the receptor/tyrosine kinase complex through its SH2 domain [10][11][12]. Many cytokines beside IFNs can activate STAT proteins to regulate gene expression [13][14][15]. In addition to JAK kinase, a variety of tyrosine kinases, such as Src, and EGF receptor tyrosine kinase have been found to activate STAT proteins [16][17][18][19].…”
Section: The Stat Signaling Pathwaymentioning
confidence: 99%
“…STAT proteins can interact with the receptor/tyrosine kinase complex through its SH2 domain [10][11][12]. Many cytokines beside IFNs can activate STAT proteins to regulate gene expression [13][14][15]. In addition to JAK kinase, a variety of tyrosine kinases, such as Src, and EGF receptor tyrosine kinase have been found to activate STAT proteins [16][17][18][19].…”
Section: The Stat Signaling Pathwaymentioning
confidence: 99%
“…This approach has been successfully used by other groups to characterize proteins binding to GAS-like sequences [12,27]. GAF, the Stat 1 dimer, is present in IFN-y-treated U937 cells and binds to the IFP53-GAS (Fig.…”
Section: Characterization Of Dif By Oligonucleotide Precipitation Andmentioning
confidence: 99%
“…The common denominator of these elements is their ability to bind a dimer of Stat 1, the gamma-interferon activation factor (GAF), [11]. However, GAS-like elements differ slightly in their DNA sequence and are thus capable of specific association with other different Stat proteins [12][13][14][15][16][17][18]. One of these GAS-like elements has originally been found in the promoters of genes that encode milk proteins and that are induced upon prolactin stimulation of mammary gland cells during lactation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Stat1 and Stat3 are both activated through the EGF receptor (4,6,8,50). Studies using the EGF receptor deletion mutants showed that two intracellular tyrosine residues (Tyr 1068 and Tyr 1086 ) are necessary for Stat activation (51) and may provide binding sites for Stats.…”
Section: Discussionmentioning
confidence: 99%